Clinical and care profiles of children and adolescents with Sickle Cell Disease in the Brazilian Northeast region - Marques,Taciana (2019)
Abstract Objectives: to describe the clinical epidemiological and care profiles of pediatric patients with sickle cell disease. Methods: a descriptive study of all (48) children and adolescents with sickle cell disease, assisted at a public referral hospital in Paraíba State. The information were obtained from the patients’ medical records and interviews were analyzed by using the Epi-Info program 7.2 version, frequency tables were built for the categorical variables and the central measurements and dispersion tendencies were calculated for the variables related to age and hospitalizations. Results: the patients’ age ranged from 15 months to 19 years old (median 8.6 years old); 91.7% considered their skin color mixed/black; 81.3% belong to D and E social class; 48% of the responsible guardians reported to have less than nine years of schooling; 70.9% lived in other cities; 93.8% received late diagnosis and 87.5% had irregular outpatient follow-up, 62,5% had an incomplete or outdated vaccination record. There were 226 hospitalizations; painful crises were the most common causes (55.7%). Each patient was hospitalized, about 5.2 times in the period; the median of total days for being hospitalized was 28. There were no deaths. Cardiac (56.2%) and hepatobiliary (54.3%) were the most common chronic compli-cations. Conclusions: sickle cell disease is a neglected clinical condition in the Brazilian Northeast region, where the appropriate political support for the patients is not fulfilled.